1995
DOI: 10.1111/j.1365-2214.1995.tb00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Language and motor development in pre‐term children: some questions

Abstract: A cohort of 37 pre-term children was assessed for both morphosyntactical and for vocabulary skills at the age of 2 and again at the age of 3 years and 6 months. They were compared with two comparison groups of full-term children (adjusted age and chronological age). The results indicated (1) a clear asynchrony between the two components of language production assessed at both ages, (2) an accurate prediction of language delay at age 2 for pre-term children (35% of pre-term children were detected for morphosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
2
5
0
3
Order By: Relevance
“…A dimensão da influência ambiental no processo do atraso tem recebido atenção por parte de pesquisadores no sentido de se buscarem dados conclusivos a respeito de fatores como o período de hospitalização do recém-nascido, suporte familiar e do psicológico materno frente ao impacto do nascimento pré-termo 7,[21][22][23] . Crawford 24 observou que aos seis meses de idade cronológica, as crianças pré-termo comportavam-se de um modo diferente das crianças de nascimento a termo.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A dimensão da influência ambiental no processo do atraso tem recebido atenção por parte de pesquisadores no sentido de se buscarem dados conclusivos a respeito de fatores como o período de hospitalização do recém-nascido, suporte familiar e do psicológico materno frente ao impacto do nascimento pré-termo 7,[21][22][23] . Crawford 24 observou que aos seis meses de idade cronológica, as crianças pré-termo comportavam-se de um modo diferente das crianças de nascimento a termo.…”
Section: Discussionunclassified
“…Siegel 2 e Ungerer e Sigman 3 foram os primeiros a estudar mais extensivamente a linguagem: comparando idade cronológica à corrigida e centralizaram o interesse na investigação do momento em que o pré-termo se iguala à criança nascida a termo, ponderando sobre os riscos e benefícios da correção, como a maioria dos estudos que se seguiram. A inclusão nos estudos específicos sobre linguagem, de variáveis como a condição de pequenos para a idade gestacional (PIG) e adequado para a idade gestacional (AIG), surgiu mais recentemente e despertou interesse, dadas as condições desfavoráveis relacionadas ao PIG, já bem estabelecidas [7][8][9][10] . Utilizando como parâmetro comportamentos receptivos e expressivos de linguagem, propostos por roteiro publicado em nosso meio 11 , a presente pesquisa tem por objetivo comparar indicadores da aquisição e desenvolvimento da linguagem receptiva e expressiva, de crianças nascidas pré-termo, sem sinais de lesão neurológica e com acuidade auditiva normal, considerando-se a idade cronológica e corrigida, e a condição de nascimento AIG ou PIG.…”
unclassified
“…Moreover, further supporting evidence for this view comes from longitudinal studies of children born prematurely. Such studies have shown that premature children have an increased likelihood of both language and motor delay and/or abnormalities later in development ( Jongmans et al 1993, Le Normand et al 1995. Indeed in a longitudinal study, Le Normand et al assessed children born prematurely at both 2 and 3 years 6 months of age, nding no correlation between language and motor performance at either age.…”
Section: Issues Arisingmentioning
confidence: 99%
“…The group with ELBW used less complex expressive language (spontaneous language samples) and showed lower receptive understanding (Peabody Picture Vocabulary Test), auditory memory and verbal reasoning in comparison with the matched control group. Also in other studies [3,4] preterm children with a birth weight of ! 1,000 g were present, but the results of the language assessments of the children at the age of 2, 3.5 and 5 years were mentioned together with the data of the preterm children with a very low birth weight and low birth weight.…”
Section: Introductionmentioning
confidence: 99%